ANALISIS KANDUNGAN ELEKTOLIT DAN NON ELEKTROLIT PADA TANAMAN OBAT KELUARGA (TOGA) - Jahro, Iis Siti; Simanullang, Selafionita; Hutagalung, Tien Parsaulian; Simanjuntak, Putrina; Sati, Naffa; Pratama, Muhammad Rizky; Daeli, Dinastini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The objectives of this study include to determine the content of electrolytes and non-electrolytes and determine the current strength in the solution of family medicinal plants. Electrolyte solutions have important benefits in human daily life, especially in foods consumed by humans that contain electrolytes and non-electrolytes. Electrolyte solutions are needed by the body so that organs can function such as the brain, nerves and muscles. The benefits of electrolytes are that they help maintain water balance and cell turgor pressure which is important for cell growth, electrolytes such as potassium, sodium, and calcium play a role in the transformation of nutrients and enzymes in plants. The benefits of non-electrolytes in plants as energy metabolism such as sugars and amino acids that play a role in the storage and use of energy, affecting the internal pH of cells and the environment. The tools used in this experiment include: multimeter, multitester prop cable, 1 9V battery, 1 small 2.5V lamp, 11 plastic cups, iron, chopper, cable, light fittings, scissors / cutter, tablespoon, sieve, grater, cardboard. Materials used are water, avocado fruit, pineapple fruit, banana fruit, lemongrass, turmeric, lemon fruit, pandan leaves, betel leaves, ginger, tomatoes, lime, and tissue. ABSTRAKTujuan penelitian ini antara lain untuk mengetahui kandungan elektrolit dan non-elektrolit serta mengetahui kuat arus pada larutan tanaman obat keluarga. Larutan elektrolit memiliki manfaat penting dalam kehidupan sehari-hari manusia terutama pada makanan yang dikonsumsi manusia yang mengadung elektrolit dan non elektrolit. Larutan elektolit dibutuhkan tubuh agar organ tubuh bisa berfungsi seperti otak, saraf dan otot. Adapun manfaat elektrolit yaitu membantu dalam menjaga keseimbangan air dan tekanan turgor sel yang penting untuk pertumbuhan sel, elektrolit seperti kalium, natrium,dan kalsium berperan dalam tranformasi nutrisi dan enzim dalam tanaman. Manfaat non- elektrolit pada tanaman sebagai metabolisme energi seperti gula dan amino yang berperan dalam penyimpanan dan penggunaan energi, mempengaruhi pH internal sel dan lingkungan. Alat yang digunakan dalam percobaan ini antara lain: multimeter,kabel prop multitester, 1 baterai 9V, 1 buah lampu kecil 2,5V, 11 buah cup plastik, besi, chopper, kabel, fitting lampu, gunting/cutter, sendok makan, saringan, parutan, kardus. Bahan yang digunakan air, buah alpukat, buah nenas, buah pisang, sereh, kunyit, buah lemon, daun pandan, daun sirih, jahe, tomat, jeruk nipis, dan tissue.